Implementación de un segmento radial de seguridad ciudadana semanal de 25 minutos de duración, en el programa a primera hora de radio Majestad - Vela Vinces, John Fabricio (2014)
This Thesis suggests the “MPLEMENTATION OF A 25 MINUTES PUBLIC SAFETY RADIAL SEGMENT IN A PRIMERA HORA PROGRAM IN RADIO MAJESTAD” The general objective of this work is to create a radial informative segment which allows the community to know the numbers of public insecurity and recommendations to deal with it seeks to structure a radio news space that allows the community talk about a very actual and sensible topic, which is Public Safety. In order to this, it proposes to transmit a specific segment in a radio news program that will dedicate 25 minutes each week to talk about it. The methods and techniques used to the data compilation and the corresponding analysis were: Scientific, Descriptive, Deductive and Statistical Model. To do this work, the techniques were surveys and interviews with an specific group of people questions related to the safety situation, their knowledge about the ways used by criminals, their studies, and their perception about the authorities work. The interview was applicated to the experts in public security Ricardo Camacho and Fernando Carrión, and allows to know the numbers and figures about the security and insecurity levels managed by specific institutions about this topic. The survey was applied 30 men and 30 women in two places of Quito: California Alta, in the north, and El Recreo in the south. Here it was determinated that 75% of consulted people don´t have the feeling of security en in the country, while 71% think the poverty is the principal cause for the crimes. 53% ranked the robbery as the main crime above the murder or fraud, but at the same time, 70% says that sometimes they have buy uncertain origin objects, across the illegal system called “cachinería”. Also, the survey established that 64% people don’t know how to act against crime, and 72% admit that don´t know the ways to deal with it. 5 Finally, the 70% thinks that the audiovisual media is the best way to spread security policies, and this is the reason which allows me to this work. With this elements, the radio, the excellence mass media, with low rates in comparation to TV, and with more scope, seems the more adequate way to promote an informative and educative space related with public security